Legal Protection of Intellectual Property Rights in Licensing Agreements in Indonesia: A Review from a Civil Law Perspective - Salim, Agus; Saputra, Agung Arafat (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2025)
This research analyzes the legal protection of intellectual property rights (IPR) within licensing agreements in Indonesia from a private law perspective. Utilizing a literature review and analysis of relevant regulations, we explore key aspects of drafting licensing agreements and their implications for IPR protection. Our findings reveal gaps in IPR protection stemming from ambiguous clauses, limited knowledge among contracting parties (especially SMEs), enforcement challenges, and the need for adaptation to new technologies. Policy reforms are essential, including agreement standardization, enhanced IPR literacy, optimization of alternative dispute resolution mechanisms, and legislative adaptation to technological dynamics, to improve the effectiveness of legal protection.